Formulation and Quality Evaluation of Sisnu (Urtica plaviflora) Soup Powder - Bhattarai, Geeta; Thapaliya, Pratigya; Khadka, Dambar Bahadur (Himalayan Journal of Science and Technology, 2017)
Abstract available on the full text PDF.